Structural and lithological controls of disseminated gold mineralization of the MEM2 deposit, Murchison Greenstone Belt, South Africa - Carlton, Luke Roos (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.